Validation of GDAP1 and HECW2 as epigenetic markers of alcohol use disorder in blood and brain - Wiegand, Ariane; Friske, Marion; Edelmann, Susanne; Bender, Annika; Fischer, Lea; Zill, Peter; Koller, Gabriele; Bakalkin, Georgy; Sommer, Wolfgang H.; Hansson, Anita C.; Nieratschker, Vanessa (International journal of molecular sciences, 2025)
Alcohol use disorder (AUD) is associated with widespread epigenetic alterations, including changes in DNA methylation (DNAm). This multi-cohort study validated and extended previous findings on DNAm of HECW2 and GDAP1 in AUD, assessed sex differences, and explored DNAm in blood and brain tissue in humans and rats. DNAm was measured via pyrosequencing in human blood (NCtrl = 341, NAUD = 258), postmortem frontal cortex (Brodmann area 9; discovery cohort: NCtrl = 10, NAUD = 13, replication cohort: NCtrl = 64, NAUD = 55) and rat blood and medial prefrontal cortex (NCtrl = 16, NAUD = 15). Gene expression was assessed in human postmortem brain by quantitative real-time PCR. AUD-associated DNAm differences in HECW2 and GDAP1 were replicated in human blood. While decreased GDAP1 DNAm was only observed in men, HECW2 hypomethylation was present in both sexes. In brain tissue, initial DNAm increases in AUD and HECW2 gene expression decreases were not validated in the replication cohort. In rats, HECW2 hypomethylation appeared in the prelimbic cortex but not in blood. Our findings support the involvement of HECW2 and GDAP1 DNAm in AUD, revealing sex-specific and tissue-dependent epigenetic patterns. The opposing DNAm directionality in blood and brain underscores the complexity of alcohol-related epigenetic modifications and suggests the need for multi-tissue, cross-species, and longitudinal studies to clarify causal mechanisms.
Veröffentlicht: 8. November 2025
Gesehen am 29.01.2026